ChemInform Abstract: Annulation Reactions of Allenyl Esters: An Approach to Bicyclic Diones and Medium‐Sized Rings. Issue 12 (March 2015) - Bhat, Bilal A.; Maki, Samantha L.; St.Germain, Elijah J.; Maity, Pradip; Lepore, Salvatore D.
Abstract The addition of allenyl esters (II) to α‐sulfonyl cycloalkanes (I) leads to lactones (III), which are converted into desired bicyclic diones (IV) by a reductive intramolecular aldol cyclization and a subsequent oxidation.